Identification of Molecular Substrate for the Attenuation of Anxiety: A Step Toward the Development of Better Anti-Anxiety Drugs - Uwe Rudolph (The Scientific World Journal)
Anxiety disorders affect some 19 million people in the U.S. alone, costing $46.6 billion, or one third of the nation’s total mental health bill in 1990. Benzodiazepine tranquilizers like the prototypic diazepam are among the most widely used anti-anxiety agents. In addition to their anxiolytic action, they also induce sedation and may impair motor coordination, both of which are undesired side effects when they are used as anxiolytics. Not surprisingly, road traffic accidents may be increased for patients on classical benzodiazepines. In addition, these drugs carry the risk of dependence liability. Benzodiazepines augment the action of the inhibitory neurotransmitter g-aminobutyric acid (GABA) at contact points between two nerve cells called synapses, points at which information is transmitted from one nerve cell to the next. Synaptically released GABA binds to postsynaptic GABAA receptors, thus causing an influx of negatively charged chloride ions into the postsynaptic neuron. This leads to a hyperpolarization and thus functional inhibition of the postsynaptic cell. Benzodiazepines bind to a site on the GABAA receptor which is different from the GABA binding site, thus increasing the chloride current. Benzodiazepines like diazepam bind to GABAA receptors containing the α subunits α1, α2, α3, or α5, most likely in abgabg combinations.